Review: Analisis Kualitatif Dan Kuantitatif Kandungan Hidrokuinon Dalam Krim Pemutih Wajah Dengan Berbagai Metode Analisis - Dea Riski Pebrianti; Dhea Syafitri Dwiyanti; Hudaynu Patya Putri; Gyna Dalila Virginia; ⁠I Gede Eka Surya Buana; Eskarani Tri Pratiwi (Universitas Muhammadiyah Klaten, 2026)
Analysis of the hydroquinone content in facial whitening cream can be carried out using qualitative and quantitative methods. Hydroquinone, although effective in reducing melanin production, is potentially dangerous if used excessively, namely it can cause skin irritation and serious health problems. Qualitative analysis can be carried out using thin layer chromatography (TLC) and color reaction methods, while quantitative analysis can use UV-Vis Spectrophotometry and High Performance Liquid Chromatography (HPLC). The results of the analysis show that many facial whitening cream products contain hydroquinone that exceeds the permitted limit (<2%), although some products are still within the safe limit. These findings emphasize the importance of strict supervision of cosmetics circulating on the market, in order to protect consumers from health risks. The choice of analytical method depends on specific needs, namely TLC is suitable for fast identification and HPLC for more accurate results on complex compounds.